Analisis Numerik Kuat Lentur Sumbu Lemah Dan Sumbu Kuat Balok Baja Profil C Kanal Menggunakan Stiffener - Tia Aurelia; Reni Suryanita; Ismed Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
One of the steel sections that is widely used is the C channel section. C channel sections are generally used as purlins. C channel beam has a large ratio of width to height. This can lead the element of structure to failure such as buckling. So, the stiffener was used on the beam to prevent buckling. This study aims to analyze the effect of using stiffener on the C channel steel section. The analysis of the effect of stiffener on flexural strength was carried out using LUSAS V18 finite element. The test object was modeled with 2 objects using stiffener and 2 objects without stiffener. The result of the numerical analysis using the LUSAS V18 finite element showed that the load capacity of B1-2 had increased by 5.88% from the B1-1. The beam in the strong axis direction without stiffeners had the maximum load of 17 kN with a deflection of 18.67 mm, while the beams with stiffeners had the maximum load of 18 kN with a deflection of 13.346 mm. In the weak axis direction, the result shows that the load capacity of B2-2 had increased by 20% from the beam B2-1. The beam B2-1 had the maximum load of 10 kN with a deflection of 18.29 mm, while the beams with stiffener had the maximum load of 12 kN with a deflection of 27.46 mm. So it can be concluded that the use of stiffeners can increase the load capacity.Keyword: C Channel Section, Stiffener, Deflection, LUSAS, Strong Axis